Robust controller design of microturbine and electrolyzer for frequency stabilization in a microgrid system with plug-in hybrid electric vehicles - Vachirasricirikul, Sitthidet; Ngamroo, Issarachai (My University, 2012)
This paper proposes a new robust controller design of microturbine (MT) and electrolyzer (ES) in a control and monitoring system (CMS) for frequency stabilization in a microgrid system with plug-in hybrid electric vehicles (PHEVs). In the studied microgrid, the MT is normally used to provide the main power to the loads while the ES absorbs the power from the system to produce the hydrogen as the fuel input for the power generation of the fuel cell. On the other hand, the large numbers of PHEVs are utilized in the consumer side. The concurrent charging powers of PHEVs cause a problem of severe frequency fluctuation in the microgrid. To solve this problem, the frequency stabilization of CMS is performed by controlling the power output of MT and ES. The controller structure of MT and ES is a proportional integral with a single input. To enhance the tracking performance and the robustness against system uncertainties of the designed MT and ES controllers, the control parameters are optimized by shuffled frog leaping algorithm based on specified-structure mixed H 2/H ∞ control technique. Simulation results not only show the frequency stabilization effect against the random charging power of PHEVs but also the high robustness of the proposed robust MT and ES controllers against the system parameters variation. © 2012 Elsevier Ltd. All rights reserved.
Keywords: Electrolyzer; Frequency stabilization; Microgrid; Mixed H 2/H ∞ control; Plug-in hybrid electric vehicle; Shuffled frog leaping algorithm